2008
DOI: 10.1002/dvg.20412
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D (Gsdmd) is dispensable for mouse intestinal epithelium development

Abstract: Members of the novel gene family Gasdermin (Gsdm) are exclusively expressed in a highly tissue-specific manner in the epithelium of skin and the gastrointestinal tract. Based on their expression patterns and the phenotype of the Gsdma3 spontaneous mutations, it is inferred that the Gsdm family genes are involved in epithelial cell growth and/or differentiations in different tissues. To investigate possible roles of the Gsdm gene family in the development of intestinal tracts, we generated a Gsdmd mutant mouse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…The loss-of-function type mouse mutants of Gsdm family genes, such as the Gsdmd KO mice in our previous study and the Gsdma KO mice in this study, show neither morphologic anomaly such as epithelial hyperplasia nor tumor development (Fujii et al 2008). The failure to identify a visible phenotype in the KO mice may be due to functional redundancy with the other genes.…”
Section: Discussionmentioning
confidence: 55%
“…The loss-of-function type mouse mutants of Gsdm family genes, such as the Gsdmd KO mice in our previous study and the Gsdma KO mice in this study, show neither morphologic anomaly such as epithelial hyperplasia nor tumor development (Fujii et al 2008). The failure to identify a visible phenotype in the KO mice may be due to functional redundancy with the other genes.…”
Section: Discussionmentioning
confidence: 55%
“…GSDMB may be involved in the regulation of the growth and differentiation of epithelial cells 40, 41 . The function of the upstream ORMDL3 gene in humans is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, a molecule, gasdermin‐D (GSDMD), has been identified as a critical player in these events. GSDMD is a highly conserved protein in mammals, although its function is unclear . GSDMD is approximately 480 amino acids long with two main domains: an N‐terminal GSDMD‐N domain and a C‐terminal GSDMD‐C domain connected by a linker loop and previously found to be cleaved by caspase‐1 .…”
Section: Non‐canonical Inflammasome Activation During Inflammatory Rementioning
confidence: 99%
“…GSDMD is a highly conserved protein in mammals, although its function is unclear. 70 GSDMD is approximately 480 amino acids long with two main domains: an N-terminal GSDMD-N domain and a C-terminal GSDMD-C domain connected by a linker loop 71 and previously found to be cleaved by caspase-1. 72 Kayagaki et al 73 reported that GSDMD plays an essential role in caspase-11 non-canonical inflammasome-dependent pyroptosis and secretion of IL-1b.…”
Section: Gasdermin D Is a Key Molecule In Caspase-11 Noncanonical Infmentioning
confidence: 99%